The Harms Beyond Imprisonment: Do We Have Special Moral Obligations Towards the Families and Children of Prisoners? - Bülow, William (2014)
This paper discusses whether the collateral harm of imprisonment to the close family members and children of prison inmates may give rise to special moral obligations towards them. Several collateral harms, including decreased psychological wellbeing, financial costs, loss of economic opportunities, and intrusion and control over their private lives, are identified. Two competing perspectives in moral philosophy are then applied in order to assess whether the harms are permissible. The first is consequentialist and the second is deontological. It is argued that both of them fails and therefore it is hard to defend the position that allowing for these harms would be morally permissible, even for the sake of the overall aims of incarceration. Instead, it is argued that these harms imply that imprisonment should only be used as a last resort. Where it is necessary, it should give rise to special moral obligations. Using the notion of residual obligation, these obligations are defended, categorized and clarified.
Keywords: Residual obligations; Philosophy of punishment; Imprisonment; doctrine of double effect; Consequentialism; Collateral harm